Brazilian Reference Percentiles for Bioimpedance Phase Angle of Healthy Individuals - Mattiello, Rita; Mundstock, Eduardo; Ziegelmann, Patrícia Klarmann (Frontiers in Nutrition, 2022)
Objectives: The present study was designed to estimate phase angle percentile curves for a broad age range of healthy individuals. Methods: This is a cross-sectional study of healthy Brazilian individuals aged five to 80. InBodyS10 was used to assess phase angle. Reference curves were stratified by sex and estimated using Generalized additive models for location, scale, and shape as a continuous function of age. The phase angle determinants analyzed were physical activity, age, BMI, and SES variables. Results: Data were analyzed from 2146 individuals, 1189 (55.2%) of whom were female. In both sexes, the phase angles showed a similar pattern (an increasing trend from childhood to the teenage phase, followed by stabilization during adult ages and a decrease in old adults). In female, the relationship between phase angle and age were associated with BMI and family income. In the male, the relationship between phase angle and age were associated with skin color and family income. Conclusions: To the best of our knowledge, it is the first attempt to apply the GAMLSS technique to estimate phase angle percentiles in a healthy population covering most of the life cycle. We also showed that there are different phase angle determinants according to sex.